The vanishing - Holt, Christopher, 1980- (Holt, Christopher, 1980- Last dogs, 2012)
When all humans in his world disappear, Max, a yellow Labrador Retriever, searches for Madame Curie who, he knows, will help find his people but as he and friends Rocky and Gizmo search, they face angry wolves, a gang of subway rats, and the Corporation, a supposed "perfect" society for dogs.